Mechanical Reinforcement of Polyethylene Using Polyethylene-Grafted Multiwalled Carbon Nanotubes - Yang, B.-X.; Pramoda, K. P.; Xu, G. Q.; Goh, S. H. (Advanced functional materials, 2007)
The incorporation of carbon nanotubes to a polymer generally improves the stiffness and strength of the polymer, but the ductility and toughness of the polymer are compromised in most cases. Here we report the mechanical reinforcement of polyethylene (PE) using polyethylene‐grafted multiwalled carbon nanotubes (PE‐g‐MWNTs). The stiffness, strength, ductility and toughness of PE are all improved by the addition of PE‐g‐MWNTs. The grafting of PE onto MWNTs enables the well‐dispersion of nanotubes in the PE matrix and improves MWNT/PE interfacial adhesion. The grafting was achieved by a reactive blending process through melt blending of PE containing 0.85 wt % of maleic anhydride and amine‐functionalized MWNTs. The reaction between maleic anhydride and amine groups, as evidenced by X‐ray photoelectron spectroscopy and Raman spectroscopy, leads to the grafting of PE onto the nanotubes. Polyethylene is grafted onto multiwalled carbon nanotubes by a reactive blending process. The stiffness, strength, ductility and toughness of polyethylene are all improved by the addition of PE‐g‐MWNTs.